First Pregnancy, Somatic and Psychological Status of a 4-Year-Old Child Born following Annexin V TESA Sperm Separation - Krzysztof Lukaszuk; Monika Wcislo; Joanna Liss; Anna Stachowicz; Grzegorz Jakiel; Mariusz Lukaszuk; Ewa Pastuszek; Izabela Woclawek-Potocka; Antonio Galvao; Dorota Bialobrzeska (Thieme Medical Publishers, Inc., 2015)
Abstract Introduction Sperm DNA integrity is a crucial paternal factor affecting fertilization and pregnancy rates, as well as embryo development. Case The present case report describes the successful pregnancy after testicular sperm aspiration (TESA) combined with intracytoplasmic sperm injection (ICSI) (TESA-ICSI) in a couple where the male presented high sperm DNA fragmentation. In order to sort damaged sperm presenting DNA fragmentation, magnetic activated cell sorting (MACS) with annexin V microbeads (MACS Miltenyi Biotec, Teterow, Germany) was used. Conclusion The authors present the first description of a successful medical case using TESA-ICSI annexin V sperm sorting. Additionally, a follow-up of the child at the age of 4 years old was done.